INTERROGATIVE SENTENCE: A CONTRASTIVE STUDY OF ARABIC AND INDONESIAN - Nikmah, Khoirin (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2019)
Involving first language (L1) in second language learning (L2) is considered as an effective method to be practiced. This research focuses on a contrastive study between Arabic and Indonesian. It aims to investigate similarities and differences of the two languages, especially about their interrogative sentence forms. It is descriptive qualitative research which applies two methods; observation and introspection method. Then, Contrastive Analysis (CA) is used to analyze the data. The result shows that similarity concept between Arabic and Indonesian is many shown on mat?, ayna, lim?dz?, and hal. Meanwhile, differences between both of them are shown on m?, man, ayy, and kayfa. As a result, it may occur errors in the use of question, errors in translating interrogative sentence, and errors in understanding question.